Earnings, productivity and inequality in Indonesia. (June 2016) - Tadjoeddin, Mohammad Zulfan
This article examines real wage-earning, productivity and earning inequality in Indonesia, focusing on differentials among provinces and economic sectors. The post-1997 Asian crisis and democratic Indonesia mimic the global trend of disconnection between wages and productivity: labour productivity continues to rise while real wage-earning stagnates or declines. This disconnection has three consequences. First, it affects income or earning distribution as confirmed by rising overall earnings inequality. Second, while it explains the conventional wisdom of an economy-wide negative relationship between real wages and employment, it is of concern that these two variables do not move in the same direction as the productivity improvements that have occurred in large and medium establishments in the manufacturing sector. Third, the disconnection between productivity and earnings growth opens a new discussion on the broader issue of quality of growth, as the data show that robust economic growth in the post-crisis Indonesia has not been accompanied by parallel improvements in the quality of employment.